Asymmetric supramolecular double-comb diblock copolymers: From plasticization, to confined crystallization, to breakout. (14th July 2017) - Hofman, Anton H.; ten Brinke, Gerrit; Loos, Katja
Abstract: The combination of asymmetric P4VP- b -PAPI diblock copolymers (i.e. f P 4 VP ≠ f PAPI ) and 3-NDP surfactants in hydrogen-bonded [poly(4-vinylpyridine)- block -poly( N -acryloylpiperidine)](3-nonadecylphenol) x (P4PA(3-NDP) x ) supramolecular double-comb diblock copolymers could potentially result in rather interesting morphologies. However, plasticization of the copolymer and the ability of 3-NDP to crystallize were found to affect their self-assembly significantly. In general, for high comb densities x, the complex's tendency to crystallize and its preference to form a flat interface dominated microphase separation. Lower values of x on the other hand gave uneven distribution of 3-NDP, resulting in a higher glass transition temperature of the P4VP block. Crystallization of 3-NDP's aliphatic tails was therefore in most cases restricted to the preferential PAPI microdomains, thereby maintaining the large length scale block copolymer morphology that was already present in the melt. Such behavior is identical to self-assembly of linear semicrystalline diblock copolymers, as in these type of systems structure formation depends on the segregation strength and relative magnitude of the order-disorder transition ( T ODT ), T g and T c, leading to mechanisms like confined crystallization or breakout. Graphical abstract: Highlights: Self-assembly of asymmetric supramolecular double-comb diblock copolymers was studied by SAXS, TEM and DSC. Analogue to conventional covalent bottlebrush block copolymers, formation of a curved interface was often avoided. The ability of the side chains to crystallize was, however, found to dominate microphase separation. Therefore, their phase behavior closely resembles that of semicrystalline block copolymers. Depending on the grafting density, breakout crystallization, confined crystallization or plasticization was observed.